Evaluation of antibiotics and benzoic acid on growth performance of nursery pigs - J E Nemechek; Michael D Tokach; Steven S Dritz; Robert D Goodband; Joel M DeRouchey; J R Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 240 weanling pigs (PIC 327 × 1050, initially 16.1 lb, 3 d postweaning) were used in a 28-d trial to evaluate the effects of benzoic acid and antibiotics on growth performance. Treatments were arranged as a 2 × 2 factorial (with or without 0.5% Vevovitall, a source of benzoic acid; DSM Nutritional Products, Parsippany, NJ), and with or without carbadox (Mecadox; Philbro Animal Health Corp., Ridgefield Park, NJ). The 4 dietary treatments included a control (1) without Mecadox or Vivovitall, (2) without Mecadox and with Vevovitall, (3) with Mecadox and without Vevovitall, and (4) with Mecadox and Vevovitall. No interactions (P>0.57) were observed between Mecadox and Vevovitall on growth performance. From d 0 to 14, there were no differences (P>0.12) in ADG or ADFI between pigs fed diets with or without Mecadox, but pigs fed Mecadox tended to have poorer (P<0.07) F/G than pigs fed diets without Mecadox. From d 14 to 28, pigs fed Mecadox had improved (P<0.01) ADG, ADFI, and F/G compared with pigs fed diets without Mecadox. Overall (d 0 to 28), pigs fed Mecadox had increased (P<0.02) ADG and ADFI. For the main effect of Vevovitall, there were no differences (P>0.11) in ADG, ADFI, or F/G during either phase or for the overall data. In conclusion, feeding Mecadox increased ADG and ADFI, but no improvements in growth were found when benzoic acid was included in the diets.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Benzoic acid; Carbadox; Nursery pig